2019
DOI: 10.1002/vms3.154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a structured individualised protocol as a potential cost‐effective diagnostic and therapeutic approach to chronic diarrhoea in the dog

Abstract: Diagnostic investigation and management of chronic diarrhoea in dogs can be cost‐prohibitive to many owners. The objectives of this study were to evaluate evidence‐based, individualised diagnostic and therapeutic protocols for management of dogs with chronic diarrhoea, where financial constraints dictate a budget‐limited approach and where more expensive approaches are deferred until simple affordable protocols are unsuccessful. Twenty‐two client‐owned dogs with chronic (minimum 2 weeks duration) untreated sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…This "best" may be based solely on experience as many common diagnostic and treatment options, including "gold-standard" ones, do not have strong evidence for their efficacy or good data on their success rates. There is a growing field of work being carried out to find evidence for the most effective SoC protocols for a variety of circumstances [23,[27][28][29][30] to expand the options and provide reassurance for veterinarians when practicing using SoC options.…”
Section: Discussionmentioning
confidence: 99%
“…This "best" may be based solely on experience as many common diagnostic and treatment options, including "gold-standard" ones, do not have strong evidence for their efficacy or good data on their success rates. There is a growing field of work being carried out to find evidence for the most effective SoC protocols for a variety of circumstances [23,[27][28][29][30] to expand the options and provide reassurance for veterinarians when practicing using SoC options.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that treatment decisions come with informed understanding of the risks and benefits of the different options. Bryan and others (2019) showed that the use of structured treatment protocols for dogs with chronic diarrhoea may help to reduce the number of dogs requiring high‐cost investigations. Such an approach is best suited to stable patients, with normal serum albumin concentration, acceptable body condition and where specific breed‐associated disease is not suspected.…”
Section: Low‐cost Therapymentioning
confidence: 99%